“Comparison of in vitro models for the study of senescence of macrophages associated with a tumor - T. V. Pukhalskaia; T. R. Yurakova; V. S. Mikhailovskaya; D. A. Bogdanova; O. N. Demidov (Медицинская иммунология, 2024)
Tumor-associated macrophages (TAMs) are an important and most represented population of immune cells in the tumor microenvironment. To a great extent, TAMs can determine the direction of the antitumor immune response; they can either additionally stimulate it or on the contrary contribute to the formation of immunosuppressive microenvironment. At the same time, under the influence of tumor cells and antitumor therapy, many cells in the tumor microenvironment (TME) can develop a state of senescence. Over the last decade, the topic of senescence and the search for therapies aimed at removing senescent cells has gained popularity. In the search for new therapeutic strategies to treat cancer, senescent cells of the immune system in the tumor microenvironment have received special attention since the presence of senescent TAMs in tumors is associated with poor prognosis and poor response to therapy. Given the relevance of studying the role of senescent immune cells in TME (in particular tumor-associated macrophages), we performed a comparative analysis of experimental protocols to obtain tumor-associated macrophages in vitro to determine the most relevant approach. We tested two protocols for obtaining macrophages from mouse bone marrow: (1) by adding conditioned medium from the L929 mouse sarcoma cell line (LCCM) (LCCM-BMDM); and (2) by adding recombinant mouse M-CSF (M-CSF-BMDM). We showed that LCCM-BMDMs, compared to M-CSFBMDMs, have increased expression of the arginase enzyme (Arg1), which can inhibit the activity of anti-tumor cytotoxic lymphocytes by depleting arginine in the tumor microenvironment. LCCM-BMDMs also exhibited increased secretion of factors characteristic of the senescence-associated secretory phenotype (SASP): IL-6 and TNF. Both Arg1 and IL-6 and TNF are markers characteristic of senescence-associated macrophages. Thus, the use of LCCM to obtain primary macrophage culture limits further steps in creating a model of tumor-associated macrophages that reflects the specific characteristics of the macrophage phenotypic response for different tumor types aAnd also limits studies of senescence formation in tumor-associated macrophages in models of carcinogenesis other than sarcoma. We believe that differentiation of macrophages in the presence of M-CSF appears to be a more preferable protocol to study TAMs and senescent TAMs to test new therapeutic strategies.